Analisis Kelayakan Finansial Rilex 168 Caffee di Kabupaten Mimika - Rusli; Boy Piter Nizu Kekri (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2023)
The objectives of this research are: 1) identify the characteristics of the Rilex Caffee business in Mimika Regency. 2) Provide an overview of the potential financial feasibility of the Rilex 168 Caffee business, which has economic potential in the future. This research uses quantitative research presented with numbers. The analytical methods used in this research are the descriptive statistics analysis method and financial analysis. The results of the study show that: 1) Entrepreneurs who are in this business are 48 years old, with a business length of between 5 years, a junior high school education level, and a total of 5 dependents. In addition, this business employs a workforce of 2 workers with a total production of 40 pieces of caffee beans (250 grams) per month, 25 cups of caffee drinks per day, 30 cups of non-caffee drinks per day, and 10 pieces of snacks per day. 2) Based on financial feasibility, know that the Rilex 168 Caffee business in Mimika Regency is worth running. Considering that the NPV value, good IRR value, and payback period invested in this project are also quite good, In addition, based on the cost and revenue structure of the Rilex 168 Caffee Business in Mimika Regency, it shows quite high cost efficiency, namely that every one rupiah of costs incurred will generate revenue greater than 1 rupiah.. Keywords: Financial Feasibility, Business